Three prerequisites of efficiency in the economy: how to surpass competitors through benchmarking - A. E. Tomaily; P. S. Filatova; K. D. Borisevich (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. In the context of growing competition and constant market changes, companies are striving to achieve higher efficiency through benchmarking. Companies can gain an advantage and strengthen their positions using this tool, which involves thorough analysis and the implementation of best practices. The three components of benchmarking efficiency – collaboration, comparison, and strategy – have become the foundation for building effective business processes. Goal. To develop a structured approach to the study and implementation of the three key elements of benchmarking (collaboration, comparison and strategy) in order to increase the competitiveness of enterprises, providing recommendations on their practical application for sustainable development in a dynamic market. Materials and methods. The study is based on data from industry enterprises, including economic indicators and the results of partner interactions. Comparative and statistical analysis, as well as synthesis and grouping, were used for data analysis.Results and discussion. The article examines the key components of benchmarking. When companies collaborate, they can share best practices and valuable data, which helps optimize internal processes. Comparison enables companies to identify their strengths and weaknesses, and using strategy based on this data allows them to adapt to market conditions and become more competitive. The study also demonstrated that benchmarking is effective in both production and non-production processes. Conclusion. Comprehensive use of benchmarking – including comparison, collaboration, and strategic planning – is an effective tool for enhancing competitiveness and achieving sustainable development. This approach allows companies to identify areas for improvement and make specific strategic decisions that support long-term success.